Secular trend of 30 years of agility and speed of girls from Ilhabela/ Tendencia secular de 30 años de agilidad y velocidad de las niñas de Ilhabela/ Tendência secular de 30 anos de agilidade e velocidade das meninas de Ilhabela - da Silva Júnior, João Pedro; Dornellas, Wesley; Oliveira Moda, Pedro Paulo; Lemos Sales, Diego Rafael; Estivaleti, Felipe; Bergamo, Raiany Rosa; Rodrigues Matsudo, Victor Keihan (Journal Health NPEPS, 2024)
Objective: to describe the 30-year secular trend of the neuromotor variables agility and speed of girls from Ilhabela. Methods: the study is part of the Mixed Longitudinal Growth and Development Project of Ilhabela. The convenience sampling consisted of 511 girls - focused on data obtained in four periods: 1988 (n=132), 1998 (n=166), 2008 (n=147), and 2018 (n=66) – aged between 10 and 11 years old. The following variables were analyzed: Weight, Height, Agility, Shuttle Run Test, and 50-meter Sprint Speed Test. One-Way ANOVA was used, followed by Scheffé’s post hoc test, with a significance level of p<0,05. Results: when analyzing the speed, we could observe a null secular trend in the comparison between the first and last decades. In terms of agility, there was a significant difference when comparing the years 1988/89 with 1998/99 and 2008/09, respectively. In addition, the comparison between 1998/99 and 2018/19 was significant, showing a positive secular trend in this variable. Conclusion: the results showed a positive secular trend only in the agility variable, showing that children became less agile over the years.